Analisis Value chain Dalam Desain Alert System Pengajuan Jabatan Fungsional Dosen - Citra Wiguna; Afandi Nur Aziz Thohari (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Information and communication technology (ICT) currently become one of the important things to increasing excellence in various fields, where one of field is education. Institut Teknologi Telkom Purwokerto (ITTP) is an educational institution that has a focus on ICT technology development.One of the ICT development conducted by ITTP is the existence of an alert system for submitting functional lecturer position. This alert system can produce competent lecturer and can pass the qualifications according to the rules set. In the construction of alert system, absolutely must be through desain, and corresponding with requirement and business process that exist in ITTP. Therefore in this study was conducted alert system design analysis for the submission of functional lecturer position. The analytical method that used is a Value chain which has been proven to increase the strategic step of the product. The result of this research is strength weakness analysis in the alert system design that useful for institution and also lecturer in order to improve the quality and level that is controlled and directed.